Analisis Usaha Tani Rumput Laut Di Desa Randusanga Wetan Kabupaten Brebes - Wahidatun, Wahidatun Khasanah; Khotimah, Khusnul; Juwanda, Muhammad (Universitas Veteran Bangun Nusantara, 2024)
Data collection techniques in this research include field observations, literature reviews, and interviews with respondents. The research population consisted of 16 seaweed farmers, with a sampling method using a census. The data obtained was analyzed using seaweed business analysis. The R/C ratio is a comparison between income and costs, which can be mathematically formulated as follows: R/C = TR/TC. With total revenue of IDR 21,800,000 and total costs of IDR 6,400,000, the R/C ratio is 3.41. This means that every Rp. 1 spent in seaweed farming can generate around Rp. 3.41 in income. Based on the criteria that an R/C ratio of more than 1 indicates that the business is feasible, seaweed farming in Randusanga Village is considered feasible and can provide significant profits from its operations. Benefits of Seaweed Farming: Based on calculations, seaweed farming in Randusanga Village can generate profits of IDR 15,400,000 in one harvest season. This profit is obtained by subtracting total costs (both fixed costs and variable costs) from total income. The calculated R/C ratio of 3.41 shows that every IDR 1 spent on seaweed farming produces around IDR 3.41 in income. This figure indicates that seaweed farming in Randusanga Village is feasible because it can provide profits of more than double the costs incurred.